MT1-MMP Expression in First-Trimester Placental Tissue Is Upregulated in Type 1 Diabetes as a Result of Elevated Insulin and Tumor Necrosis Factor-α Levels - Hiden, Ursula; Glitzner, Elisabeth; Ivanisevic, Marina; Djelmis, Josip; Wadsack, Christian; Lang, Uwe; Desoye, Gernot (Diabetes (New York, N.Y.), 2008)
MT1-MMP Expression in First-Trimester Placental Tissue Is Upregulated in Type 1 Diabetes as a Result of Elevated Insulin and Tumor Necrosis Factor-α Levels Ursula Hiden 1 , Elisabeth Glitzner 1 , Marina Ivanisevic 2 , Josip Djelmis 2 , Christian Wadsack 1 , Uwe Lang 1 and Gernot Desoye 1 1 Department of Obstetrics and Gynecology, Medical University of Graz, Austria 2 Department of Obstetrics and Gynecology, University Hospital, Petrova, Zagreb, Croatia Address correspondence and reprint requests to Ursula Hiden, MSc, PhD, Department of Obstetrics and Gynecology, Medical University of Graz, Auenbruggerplatz 14, 8036 Graz, Austria. E-mail: ursula.hidenatklinikum-graz.at Abstract OBJECTIVE —In pregestational diabetes, the placenta at term of gestation is characterized by various structural and functional changes. Whether similar alterations occur in the first trimester has remained elusive. Placental development requires proper trophoblast invasion and tissue remodeling, processes involving matrix metalloproteinases (MMPs) of which the membrane-anchored members (MT-MMPs) such as MT1-MMPs are key players. Here, we hypothesize a dysregulation of placental MT1-MMP in the first trimester of type 1 diabetic pregnancies induced by the diabetic environment. RESEARCH DESIGN AND METHODS —MT1-MMP protein was measured in first-trimester placentas of healthy ( n = 13) and type 1 diabetic ( n = 13) women. To identify potential regulators, first-trimester trophoblasts were cultured under hyperglycemia and various insulin, IGF-I, IGF-II, and tumor necrosis factor-α (TNF-α) concentrations in presence or absence of signaling pathway inhibitors. RESULTS —MT1-MMP was strongly expressed in first-trimester trophoblasts. In type 1 diabetes, placental pro–MT1-MMP was upregulated, whereas active MT1-MMP expression was only increased in late first trimester. In isolated primary trophoblasts, insulin, IGF-I, IGF-II, and TNF-α upregulated MT1-MMP expression, whereas glucose had no effect. The insulin effect was dependent on phosphatidylinositol 3-kinase, the IGF-I effect on mitogen-activated protein kinase, and the IGF-II effect on both. CONCLUSIONS —This is the first study reporting alterations in the first-trimester placenta in type 1 diabetes. The upregulated MT1-MMP expression in type 1 diabetes may be the result of higher maternal insulin and TNF-α levels. We speculate that the elevated MT1-MMP will affect placental development and may thus contribute to long-term structural alterations in the placenta in pregestational diabetes. DMEM, Dulbecco's modified Eagle's medium ECM, extracellular matrix ERK, extracellular signal–related kinase GRO, growth-regulated protein hCG, human chorionic gonadotropin HIF-1, hypoxia-inducible factor 1 IL, interleukin MAPK, mitogen-activated protein kinase MEK1, MAPK/ERK kinase 1 MMP, matrix metalloproteinase PI 3-kinase, phosphatidylinositol 3-kinase RPL30, ribosomal protein L30 TNF-α, tumor necrosis factor-α Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 17 October 2007. DOI: 10.2337/db07-0903. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted October 3, 2007. Received July 4, 2007. DIABETES